(3LhGH Yf GNJdGa GdeYJRdIs - (3GdbGSe Hf EHQGgje Hf ESeGYjd GdMSfj GdYdhj, CHh eMeO, GdeYQha HGdQSj,J (B246 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Cgd GdKfGA hGdeLO hHYO abO SCfdi HYV GdENhGf GdUGdMjf ai ENJdGa GdeYJRdI hGdCTYQjI ai MeO Gdgd JYGdi Ydi GdEjeGf s
(3BNQgG (B:s
(3hbO CMSf GdLhjfi hgOi GdSDGd Ydjg abGd ai GdHQgGf hGdeO ddg QH GdYGdejf hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B171 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B91s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds